Report of the Seminar on Employment of Scheduled Castes and Scheduled Tribes - Planning Commission (Planning Commission, 1961)
One of die important objectives of planning in India is the creation of adequate employment opportunities. The experience of the first two Plans has shown that in discussing the employment problem an overall national approach is inadequate. There are problems relating to special areas as also to specific communities. While the overall approach may help in determining the size of the total investment and priorities of development keeping the short-term and long-term employment perspective, it is these special categories, which call for action in different geographical regions or in case of certain communities which, due to certain handicaps, have been able to secure an appropriate share of the employment opportunities created by development.
Government of India, Planning Commission